2008
DOI: 10.1007/s00248-008-9452-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Mating of Cryptococcus neoformans var. grubii on Woody Debris

Abstract: A total of 36 Cryptococcus neoformans strains originating from South Africa were screened for wood degrading enzymes. All strains tested positive for cellulase activity while none where capable of xylan degradation. Three C. neoformans var. grubii strains, originating from clinical and environmental samples, representing the same genotype (VNI/AFLP1-C. neoformans var. grubii) and MATalpha, were evaluated for growth on debris of two common tree species in South Africa: Acacia mearnsii and Eucalyptus camaldulens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Environmental isolates have been obtained from Africa (33,(110)(111)(112), Asia (76,77,108), Australia (26,110,(113)(114)(115)(116)(117)(118), Europe (110,119,120), North America (38,110,121), and South America (122). In addition, it has been shown that plant material promotes fertility (108,(123)(124)(125) and may render C. gattii strains more pathogenic (125). Molecular types VGI and VGII are those most commonly associated with a wide variety of tree species (74,110,126).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Environmental isolates have been obtained from Africa (33,(110)(111)(112), Asia (76,77,108), Australia (26,110,(113)(114)(115)(116)(117)(118), Europe (110,119,120), North America (38,110,121), and South America (122). In addition, it has been shown that plant material promotes fertility (108,(123)(124)(125) and may render C. gattii strains more pathogenic (125). Molecular types VGI and VGII are those most commonly associated with a wide variety of tree species (74,110,126).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Geographic distribution of the molecular types identified in Africa (c). Molecular typing data have been combined from the following references: Senegal [14], Republic Democratic of Congo [11, 53], Uganda [53, 57], Rwanda [11], Tanzania [53], Malawi [53, 58, 59], Zimbabwe [11], Botswana [53, 58, 60, 61], and South Africa [11, 15, 38, 60, 62, 63]. …”
Section: Figurementioning
confidence: 99%
“…It is not known if Malassezia has a similar life cycle. However, Cryptococcus isolates are often associated with trees (in particular, Eucalyptus) (33,87,100), and the recent demonstration that Cryptococcus can complete its life cycle when cultured on woody debris (25) suggests that there may be a general link between plants and mating in some of the Basidiomycota.…”
Section: Malassezia and Ustilagomentioning
confidence: 99%